2012
DOI: 10.1007/s12672-012-0122-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Neu-Induced Mammary Carcinogenesis in Transgenic Mice Expressing ERΔ3, a Dominant Negative Estrogen Receptor α Variant

Abstract: The estrogen receptor α (ERα) splicing variant with an in-frame deletion of exon 3 (ERΔ3) is frequently expressed in the normal breast, but its influence on tumorigenesis has not been explored. In vitro, ERΔ3 has dominant negative activity, suggesting it may suppress estrogen stimulation in the breast. ERΔ3 may inhibit classical signaling on estrogen response element (ERE)-regulated genes as well as activate non-classical pathways at Sp1 and AP-1 sites. Transgenic mice were developed that express mouse ERΔ3 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Loss of expression or function of several signaling molecules inhibits lung metastasis of mammary tumors in ErbB2/Neu overexpressing mice. These include protein tyrosine phosphatase 1B (PTP1B), adapter protein Gab2, EphA2 receptor tyrosine kinase, Rho GTPase activating protein p190B, receptor activator of nuclear factor- KB (RANK), estrogen receptor α, semaphorin receptor plexin-B1, and Rac specific guanidine nucleotide exchange factor DOCK1 [142,143,144,145,146,147,148,149], underlining the role of several signaling pathways in ErbB2-induced invasion and metastasis.…”
Section: Invasive Signaling Of Erbb2mentioning
confidence: 99%
“…Loss of expression or function of several signaling molecules inhibits lung metastasis of mammary tumors in ErbB2/Neu overexpressing mice. These include protein tyrosine phosphatase 1B (PTP1B), adapter protein Gab2, EphA2 receptor tyrosine kinase, Rho GTPase activating protein p190B, receptor activator of nuclear factor- KB (RANK), estrogen receptor α, semaphorin receptor plexin-B1, and Rac specific guanidine nucleotide exchange factor DOCK1 [142,143,144,145,146,147,148,149], underlining the role of several signaling pathways in ErbB2-induced invasion and metastasis.…”
Section: Invasive Signaling Of Erbb2mentioning
confidence: 99%
“…Twenty-three studies were identified that evaluated mammary tumorigenesis following the administration of soy-based diets or purified isoflavones during postnatal development; fourteen using chemical carcinogens in rats [69,70,71,72,73,74,75,76,77,78,79,80,81,82] and nine using transgenic mice [83,84,85,86,87,88,89,90,91]. For this review, postnatal administration was defined by the initiation of soy-based diets or isoflavones at weaning or later and the design of these studies and the main findings are summarized in Table 1.…”
Section: Mammary Tumor Development Following Postnatal Soy Isoflavmentioning
confidence: 99%
“…The findings were also highly variable in the transgenic mouse models with four of the nine studies showing at least some protective effect against mammary tumorigenesis (tumor incidence, latency, multiplicity or size) [83,86,87,88], with two of these studies observing a significant decrease in tumor incidence [83,88]. Three of the studies found no effect [84,89,91] and three of the studies found that soy isoflavones promoted at least one mammary tumor property [83,85,90]. The transgenic data was more difficult to evaluate as often other characteristics (i.e., high fat diet, estrogen levels) and different concentrations of isoflavones were assessed in the same study.…”
Section: Mammary Tumor Development Following Postnatal Soy Isoflavmentioning
confidence: 99%
“…This study found that soy significantly induced mammary tumor development in the low estrogen group, inhibited mammary tumor development in the high estrogen group and had no effect on the moderate estrogen group [ 27 ]. Another study using MMTV-erbB2 transgenics showed that initiating a soy diet at 2 months of age had no effect on mammary tumor development compared to a soy-free diet [ 28 ].…”
Section: Introductionmentioning
confidence: 99%